Analisis Spasial Peluang Lokasi Unit Sekolah Baru Menggunakan Metode Score dan Sistem Informasi Geografis - Nailis Sa’adah; Yeni Yanti; Zulfan Zulfan; Susmanto Susmanto; Munawir Munawir; Irawati Irawati (Infotekmesin, 2022)
School is a formal educational institution recognized by the Indonesian State Education Institute, every citizen has the right to get it. In accordance with field interview observations, there is no equal distribution of junior high school locations around sub-districts in Aceh Besar and the distance of school locations from students' residences is very far. The purpose of this study is to analyze geographic information systems (GIS) on the probability of building new school in Aceh district, which are divided in 4 criterias; high, medium, low, and no probability, as well as using school spatial analysis (buffer, overlay and clip) and scoring methods to determine the probability for the location of the new school. The results show 4 criteria for the location probability; there are 11 districts with high probabilities, 21 medium probabilities, 23 low probabilities, and 23 no probabilities in each district.